Green Synthesis of Silver Nanoparticles from the Extracts of Fruit Peel of Citrus tangerina, Citrus sinensis, and Citrus limon for Antibacterial Activities - Moira Carmalita Dharsika Niluxsshun; Koneswaran Masilamani; Umaramani Mathiventhan (Bioinorganic Chemistry and Applications)
Wide application of nanoparticles motivates the need for synthesising them. Here, a nontoxic, eco-friendly, and cost-effective method has been established for the synthesis of silver nanoparticles using extracts of lemon peel (Citrus limon), green orange peel (Citrus sinensis), and orange peel (Citrus tangerina). The synthesised nanoparticles have been characterised using UV-visible absorptionspectroscopy, Fourier transform infrared spectroscopy, and transmission electron microscopy (TEM). The UV-visible absorption spectrum of these synthesised silver nanoparticles shows an absorption peak at around 440 nm. TEM images show different shaped particles with various sizes. Furthermore, the antibacterial activity of silver nanoparticles was appraised by a well-diffusion method and it was observed that the green synthesised silver nanoparticles have an effective antibacterial activity against Escherichia coli and Staphylococcus aureus. The outcome of this study could be beneficial for nanotechnology-based biomedical applications.